2017
DOI: 10.1016/j.ymthe.2017.06.028
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The YY1-HOTAIR-MMP2 Signaling Axis Controls Trophoblast Invasion at the Maternal-Fetal Interface

Abstract: We aimed to determine the effect of YY1 expression on the expression profile of long noncoding RNAs (lncRNAs) in trophoblasts, and we studied the involvement of certain lncRNAs and YY1 in the pathogenesis of recurrent miscarriage (RM). RT2 lncRNA PCR arrays revealed that YY1 overexpression in trophoblasts significantly promoted the expression of the HOX transcript antisense RNA HOTAIR and demonstrated that HOTAIR expression was significantly lower in the RM trophoblasts than in control trophoblasts. Ectopic HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 32 publications
0
52
0
Order By: Relevance
“…We also found that HOTAIR regulates trophoblast migration and invasion, thereby contributing to the pathology of RM and/or pre-eclampsia, suggesting HOTAIR to be a potential therapeutic target for RM. 15 This indicates that HOTAIR acts as an important non-coding RNA (ncRNA); however, the regulatory mechanisms controlling HOTAIR stability are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that HOTAIR regulates trophoblast migration and invasion, thereby contributing to the pathology of RM and/or pre-eclampsia, suggesting HOTAIR to be a potential therapeutic target for RM. 15 This indicates that HOTAIR acts as an important non-coding RNA (ncRNA); however, the regulatory mechanisms controlling HOTAIR stability are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One potential concern is that GDC-0941 is known as a potent inhibitor of PI3K/AKT pathway, which inhibits both PI3K and AKT phosphorylations as well as the downstream targets of AKT signaling, 45,46 and some researchers also use GDC-0941 as a p-AKT inhibitor. 47 However, there is a defect in this study that we did not use specific p-AKT inhibitors such as AZD5363 or GDC-0068 to elaborate our findings mechanistically more in depth.…”
Section: Discussionmentioning
confidence: 94%
“…The number of migrated cells decreased in the BPDE-treated group in a dose-dependent manner ( Figure 4(c) ). Previous studies have suggested that the PI3K/AKT/MMP2 signaling pathway was involved in trophoblast migration [ 19 ]. To determine whether BPDE inhibits trophoblast cell migration through this pathway, the mRNA levels of PI3K, AKT, and MMP2 were analyzed by qRT-PCR assays.…”
Section: Resultsmentioning
confidence: 99%